ImpactOf Covid-19 OnIndianStock Market - kanakaLaxmi, B.; Naveen Kumar Reddy, M. (International Journal of Psychosocial Rehabilitation, 2021)
“The COVID-19 pandemic has resulted all over 181,930,736 coronavirus cases and over 3,945,832 coronavirus deaths globally. Due this all over the world, all the countries are facing problems that may lead to the economic crisis and recession. The present study has been focused on impact of the COVID-19 pandemic on the Indian stock market. The major objective of the study is to what extent the Indian stock market indices are influenced by COVID-19. The study has considered the different indexes of NSE (Nifty 50 Index, Nifty AUTO Index, Nifty Bank Index, Nifty PHARMA, Nifty FMCG, Nifty IT Index, and Nifty METAL Index). The study has been considered only six months of data for the analysis and the study find that due to COVID-19, only the Nifty 50 Index, Nifty PHARMA Index Nifty IT Index and Nifty METAL Index are performing well, so it is suggested to the investors to invest in this sectors.”